Impacts of life satisfaction, job satisfaction and the Big Five personality traits on satisfaction with the indoor environment. (15th March 2022) - Cheung, Toby; Graham, Lindsay T.; Schiavon, Stefano
Abstract: Providing indoor environmental quality (IEQ) that satisfies building occupants is an essential component for sustainable and healthy buildings. Existing studies mainly analyse the importance of environmental factors on occupant satisfaction, but often overlook the influence of personal factors. Here, we aim to explore the impact of personal factors like life satisfaction, job satisfaction, the Big Five personality traits, sex, and age on occupant IEQ satisfaction. We conducted a cross-sectional assessment in nine air-conditioned commercial buildings in Singapore and surveyed 1162 individuals on their satisfaction with 18 IEQ parameters. Using proportional odds ordinal logistic regression, we found that occupants with higher job and life satisfactions were, respectively, 1.3–2.3 and 1.3–2 times more likely satisfied with the 18 IEQ parameters. The odds ratios (OR) for overall environment satisfaction and job and life satisfaction were 2.1 (95% CI: 1.8–2.6) and 1.9 (95% CI: 1.6–2.3). We speculate that occupants' satisfaction with their job and the overall environment are entwined, meaning that a better workspace could improve job satisfaction and vice versa. We observed some associations between the Big Five personality traits and some IEQ parameters, but the corresponding effects were small. Due to the substantial relationship between job and overall workspace satisfaction observed in this study, we recommend including job satisfaction questions in future post occupancy evaluations (POEs). Graphical abstract: Image 1 Highlights: We conducted post-occupancy surveys in 9 buildings (1162 respondents) in Singapore. Occupants high in job satisfaction are 1.3–2.3 times more satisfied with IEQ. Occupants high in life satisfaction are 1.3–2 times more satisfied with IEQ. Weak relationships between the Big Five personality traits and IEQ satisfaction. Recommend including occupants job satisfaction questions in future POE assessments.